Nature of PEVK-titin elasticity in skeletal muscle - Linke, Wolfgang A. (The National Academy of Sciences, 1998)
A unique sequence within the giant titin molecule, the PEVK domain, has been suggested to greatly contribute to passive force development of relaxed skeletal muscle during stretch. To explore the nature of PEVK elasticity, we used titin-specific antibodies to stain both ends of the PEVK region in rat psoas myofibrils and determined the region’s force-extension relation by combining immunofluorescence and immunoelectron microscopy with isolated myofibril mechanics. We then tried to fit the results with recent models of polymer elasticity. The PEVK segment elongated substantially at sarcomere lengths above 2.4 μm and reached its estimated contour length at ≈3.5 μm. In immunofluorescently labeled sarcomeres stretched and released repeatedly above 3 μm, reversible PEVK lengthening could be readily visualized. At extensions near the contour length, the average force per titin molecule was calculated to be ≈45 pN. Attempts to fit the force-extension curve of the PEVK segment with a standard wormlike chain model of entropic elasticity were successful only for low to moderate extensions. In contrast, the experimental data also could be correctly fitted at high extensions with a modified wormlike chain model that incorporates enthalpic elasticity. Enthalpic contributions are likely to arise from electrostatic stiffening, as evidenced by the ionic-strength dependency of titin-based myofibril stiffness; at high stretch, hydrophobic effects also might become relevant. Thus, at physiological muscle lengths, the PEVK region does not function as a pure entropic spring. Rather, PEVK elasticity may have both entropic and enthalpic origins characterizable by a polymer persistence length and a stretch modulus.